Could a residential wood ash recycling programme be part of the solution to calcium decline in lakes and forests in Muskoka (Ontario, Canada)? - Shakira S.E. Azan; Norman D. Yan; Martha P. Celis-Salgado; Shelley E. Arnott; James A. Rusak; Peter Sutey (Canadian Science Publishing, 2019)
One possible solution to the recent decline of calcium (Ca) concentrations in Canadian Shield forests and lakes in eastern North America is the addition of Ca-rich wood ash to watersheds. We investigated the feasibility of using small, mainly residential sources of non-industrial wood ash (NIWA) for this purpose by quantifying concentrations of its major nutrients and metals, its toxicity to Daphnia in aqueous extracts, and estimating the amount of NIWA available in the District of Muskoka in central Ontario. Locally collected NIWA averaged 30% Ca, and also contained smaller but significant amounts of K, Mg, Na, and P. Of these, K was so soluble that it was toxic to Daphnia over 48 h in the concentrate and 10-fold dilution; however, sedimented ash was not toxic over 15 d. Most metal levels in NIWA were below targets permitting unrestricted land application. However, Cu and Zn were just above these targets, but well below those for conditional use. Muskoka residents generate about 235 000 kg of NIWA annually, not enough to treat all central Ontario areas affected; however, a NIWA recycling programme implemented across southern Ontario could generate enough ash to solve the Ca decline problem in Muskoka's forests and lakes.